Voriconazole plus terbinafine combination antifungal therapy for invasive Lomentospora prolificans infections: analysis of 41 patients from the FungiScope® registry 2008–2019. (June 2020) - Jenks, J.D.; Seidel, D.; Cornely, O.A.; Chen, S.; van Hal, S.; Kauffman, C.; Miceli, M.H.; Heinemann, M.; Christner, M.; Jover Sáenz, A.; Burchardt, A.; Kemmerling, B.; et al.
Abstract: Objectives: Lomentospora prolificans is an emerging cause of serious invasive fungal infections. Optimal treatment of these infections is unknown, although voriconazole-containing treatment regimens are considered the treatment of choice. The objective of this study was to evaluate the role of combination antifungal therapy for L. prolificans infections. Methods: We performed a retrospective review of medical records of patients with invasive L. prolificans infection diagnosed between 1 January 2008 and 9 September 2019 that were documented in the FungiScope® registry of rare invasive fungal infections. We compared clinical outcomes between antifungal treatment strategies. Results: Over the study period, 41 individuals with invasive L. prolificans infection from eight different countries were documented in the FungiScope® registry. Overall, 17/40 (43%) had treatment response/stable disease and 21/40 (53%) had a fatal outcome attributed to invasive fungal infection. Combination antifungal therapy was associated with increased 28-day survival (15/24 survived versus 4/16 receiving monotherapy; p 0.027) and the combination voriconazole plus terbinafine trended to be associated with higher rates of treatment success (10/16, 63%, 95% CI 35%–85%) compared with other antifungal treatment regimens (7/24, 29%, 95% CI 13%–51%, p 0.053). In Kaplan–Meier survival analysis there was a higher survival probability in individuals receiving the voriconazole/terbinafine combination compared with other antifungal regimens (median survival 150 days versus 17 days). Conclusions: While overall mortality was high, combination antifungal treatment, and in particular combination therapy with voriconazole plus terbinafine may be associated with improved treatment outcomes compared with other antifungal regimens for the treatment of invasive L. prolificans infections.